Pengaruh Luas Lahan, Jumlah Produksi, Kurs Dollar Amerika Serikat dan Inflasi Terhadap Ekspor Kakao Indonesia Kurun Waktu 1994-2013 - Berata, I Kadek Edi Wirya; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 1, Januari 2017 (pp. 1 - 114), 2017)
The aim of this study is the first to investigate the influence of land area, the amount of production, the US dollar exchange rate and inflation on Indonesian cocoa exports simultaneously. Second, to determine the effect of land area, the amount of production, the US dollar exchange rate and inflation on cocoa exports partially. Third, to determine the independent variables were the dominant influence on cocoa exports Indionesia the period 1994-2013. The data used is secondary data. Data processed by multiple linear regression analysis techniques that were previously equipped with the classical assumption. The test results with SPSS obtain the results of land area, the amount of production, the US dollar exchange rate and inflation simultaneously significant effect on exports of cocoa. Partially land positive and significant impact on exports of cocoa, the amount of production and significant positive effect on exports of cocoa, the United States dollar exchange rate has no significant effect on exports of cocoa, inflation is not significant with exports of cocoa. R2 of 0.968 with a mean of 96.8 percent.
Keywords: Export; Land; Total Production; Exchange rate US Dollar; Inflation